THE DEVELOPMENT OF TABLE TENNIS LEARNING MODEL FOR IMPROVING THEORY AND PRACTICE BASED ON SCIENTIFIC CHARACTER - Rizky Bagus Santoso (Sriwijaya University Learning and Education International Conference, 2018)
This research aimed to obtain information about the initial ability of high school students include affective, cognitive, and psychomotor. The design in this research using research and development model approach. The subjects used in this study are all students of first grade in Senior High School Bina Warga 1 and Senior High School Bina Warga 2 Palembang totaling 30 people. The research method is a development study that refers to the development model of Borg & Gall, then the instruments used to collect at the stage: (1) needs analysis, (2) expert evaluation (initial product evaluation), (3) small group trial and (4) large group trials. The result of this research has fulfilled the aspect of validity, effectiveness, practicality with good score 76,8%, valuation rubric aspect 80, 22% good category, for pulse using SPSS 17 p value 0.000